2012
DOI: 10.1371/journal.pone.0035459
|View full text |Cite
|
Sign up to set email alerts
|

Immunomodulatory Effects of Bone Marrow-Derived Mesenchymal Stem Cells in a Swine Hemi-Facial Allotransplantation Model

Abstract: BackgroundIn this study, we investigated whether the infusion of bone marrow-derived mesenchymal stem cells (MSCs), combined with transient immunosuppressant treatment, could suppress allograft rejection and modulate T-cell regulation in a swine orthotopic hemi-facial composite tissue allotransplantation (CTA) model.Methodology/Principal FindingsOutbred miniature swine underwent hemi-facial allotransplantation (day 0). Group-I (n = 5) consisted of untreated control animals. Group-II (n = 3) animals received MS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
49
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(49 citation statements)
references
References 19 publications
0
49
0
Order By: Relevance
“…It is also possible that the early management of rejection increases the long-term survival and outcomes of a skincontaining VCA. It has been reported that the bone marrow component of the VCA graft may confer immunogenic protection, and investigations including bone marrow infusions or bone marrow-derived mesenchymal stem cells have resulted in tolerance to VCA grafts, however, not without complications related to graft vs. host disease and post transplant lymphoproliferative disorders [40][41][42][43].…”
Section: Tissue Type Compositionmentioning
confidence: 99%
“…It is also possible that the early management of rejection increases the long-term survival and outcomes of a skincontaining VCA. It has been reported that the bone marrow component of the VCA graft may confer immunogenic protection, and investigations including bone marrow infusions or bone marrow-derived mesenchymal stem cells have resulted in tolerance to VCA grafts, however, not without complications related to graft vs. host disease and post transplant lymphoproliferative disorders [40][41][42][43].…”
Section: Tissue Type Compositionmentioning
confidence: 99%
“…The immunosuppressive effect and low immunogenicity of mesenchymal stem cells (MSCs) make them ideal candidates for immunosuppressive strategies [3,4]. Adult MSCs have been used widely in the allogeneic heart [5][6][7][8][9][10][11], liver [12], islet [13][14][15][16][17], kidney [18,19], and composite tissue transplants [20,21]. Bone marrow mesenchymal stem cells (BM-MSCs) alone prolong heart allograft survival [8].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the very nature of a skin-bearing allograft being visible to the patient allows for continuous monitoring for signs of rejection, which would likely be a benefit when undertaking clinical trials of MSC therapy or minimization protocols. While there are no active clinical trials using exclusively MSCs for VCA, several preclinical studies have demonstrated a marked immunosuppressive effect of systemically delivered MSCs following VCA on the incidence and severity of acute rejection, the peripheral blood T regulatory response, inflammatory cytokine expression profile, and ultimately allograft survival [2,59,61,63]. These promising findings serve as a foundation for eventual translation of MSC therapy to clinical cases.…”
Section: Applications Of Mscs In Solid-organ Transplant and Vcamentioning
confidence: 99%